Mental health problems and socioeconomic disadvantage: a controlled household study in rural Ethiopia - Yohannes Hailemichael; Charlotte Hanlon; Kebede Tirfessa; Sumaiyah Docrat; Atalay Alem; Girmay Medhin; Abebaw Fekadu; Crick Lund; Dan Chisholm; Damen Hailemariam (BMC, 2019)
Abstract Background There is a lack of high quality population-based studies from low- and middle-income countries examining the relative economic status of households with and without a member with a mental health problem. The aim of the study was to explore the socio-economic status of households with a person with severe mental disorder (SMD; psychosis or bipolar disorder) or depression compared to households without an affected person. Methods A population-based, comparative, cross-sectional household survey was conducted in Sodo district, south Ethiopia, between January and November 2015. Two samples were recruited, each with its own comparison group. Sample (1): households of 290 community-ascertained persons with a clinician-confirmed diagnosis of SMD and a comparison group of 289 households without a person with SMD. Sample (2): households of 128 people who attended the primary health care centre and who were identified by primary care staff as having a probable diagnosis of depressive disorder; and comparison households of 129 patients who attended for other reasons and who did not receive a diagnosis of depression. Household socioeconomic status (household income, consumption and asset-based wealth) was assessed using a contextualized version of theWorld Health Organization (WHO) Study on global Ageing and adult health (SAGE) questionnaire. Each disorder group (SMD and depression) was further divided into higher and lower disability groups on the basis of median score on the WHO Disability Assessment Schedule. Results Households of a person with SMD who had higher disability were more likely to have a poorer living standard (no toilet facility; p < 0.001). Having a reliable source of regular income was significantly lower in households of a person with SMD (p = 0.008) or depression (p = 0.046) with higher disability than the comparison group. Households of persons with SMD with higher disability earned less (p = 0.005) and owned significantly fewer assets (p < 0.001) than households without SMD. Households including persons with depression who had higher disability had lower income (p = 0.042) and reduced consumption (p = 0.048). Conclusions Households with a member who had either SMD or depression were socioeconomically disadvantaged compared to the general population. Moreover, higher disability was associated with worse socio-economic disadvantage. Prospective studies are needed to determine the direction of association. This study indicates a need to consider households of people with SMD or depression as a vulnerable group requiring economic support alongside access to evidence-based mental healthcare.